Colleges and schools-College of Arts and Humanities-Music-0031
Arthur C. Berdahl 1st Couait 1948-1949-Oct. 19, 1948. Hymnand Tusuinl Tune-Cowell Tschaikowiky. Symph. No.4- Conuito no3. Eight-Mojar to Hointoich James Winter, soloist Oueituie, Ruy Blas-Meudalsshohu